China pluperfect. - Vigneron, Frank (The Chinese University of Hong Kong Press, 2022)
"This book contains analysis of different domains of contemporary art in China seen through the lens of the epistemological changes described in China Pluperfect I: Epistemology of Past and Outside in Chinese Art.It first looks at the concept of "ink art," describing how it meant different things to different people in the former colony and how these different meanings came to determine certain institutional choices made at the beginning of the 21st century. The following chapters are dedicated to issues related to the urban and rural contexts for art creation in Mainland China and Hong Kong. One chapter observes the ups and downs of the representations of cities in the history of the People's Republic of China and how they have defined a certain idea of culture. Another looks at how Chinese cities have been exceptional centers of art creations over the last thirty to forty years through the example of Shenzhen where a vibrant art scene, albeit closely connected to Hong Kong which has become a major art hub in the last two decades, has developed. The following is dedicated to the changing fortunes of art making in the countryside, observing how institutions in the Mainland and in Hong Kong have supported these practices very differently.Frank Vigneron finally considers how the different speeds of globalization, slow in the past and fast today, have determined some of the issues of past and outside in the present, particularly in the context of socially engaged art in both the Mainland and Hong Kong."--Pulisher.